Assessing biofilm formation by Listeria monocytogenes - Fouladynezhad, Nina; Afsah Hejri, Leili; Rukayadi, Yaya; Mohammed, Abdulkarim Sabo; M. N., Marian; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
Listeria monocytogenes(L. monocytogenes) is a serious food-borne pathogen for immunocompromised individuals. L. monocytogenes is capable of producing biofilm on the surface of food processing lines and instruments. The biofilm transfers contamination to food products and impose risk to public health. Transfers contamination to food products, and impose risk hazard to public health. The aim of this study was to investigate biofilm producing ability of L. monocytogenes isolates. Microtitre assay was used to measure the amount of biofilm production by ten L. monocytogenes isolates from minced chicken / meat, sausages and burgers. Results showed that all 10 L. monocytogenes isolates were able to form biofilm after 24 h at 20 ̊C on polystyrene surface (the common surface in food industries). Some strains were capable of forming biofilm more than the others. All strains showed a slight raise in the quantities of attached cells over 48 and 72 h. L. monocytogenes strains isolated from minced chicken, minced meat and burgers were better biofilm-producers comparing to the strains isolated from sausages.